Relationship parent support and peer with student learning discipline - Wulandari, Lulu Retno (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2018)
Any student who has been learning discipline will be able to steer itself and control the behavior. Parent support not only provides the school facility, but can help to learn and solve problems together. Peer support has an important role in the establishment of norms for better or worse against the students have regularity in learning. The purpose of this study was, 1) to describe the parent support, peer support, and learning discipline, 2) examine the relationship of parent support with the learning discipline, 3) examine the relationship peer support with the learning discipline, and 4) examine the relationship of parent support and peer with the learning discipline. This study used a descriptive correlation quantitative method. The samples in this study of 192 people, selected by proportional stratified random sampling technique. Data were analyzed using descriptive statistics, simple regression, and multiple regressions.